Comparative Life History Parameters of Three Stink Bug Pest Species. Issue 2 (17th March 2022) - Daane, Kent M; da Silva, Paul G; Stahl, Judith M; Scaccini, Davide; Wang, Xingeng
Abstract: California pistachios are threatened by several stink bug species (Hemiptera: Pentatomidae), including the native Thyanta pallidovirens (Stål) and Chlorochroa uhleri (Stål), as well as the invasive Nezara viridula (L.). In pistachio, control tactics often target specific life stages, which makes knowledge about life histories fundamental to successful IPM programs. For that purpose, life history parameters of these stink bug species were assessed. Nymphal development and survivorship at seven constant temperatures, upper and lower development thresholds, thermal constants, adult longevity and fecundity, and life table parameters were evaluated. No species completed development at 15°C or 35°C. For N. viridula, egg to adult development was fastest at 30°C, whereas for T. pallidovirens there was no significant difference between 27.5 and 30°C and C. uhleri development was similar between 25 and 30°C. Egg to adult survival was highest at 22.5°C and 27.5°C. The thermal requirements as degree-days (DD) to complete immature development were estimated to be 714.3, 370.4, and 434.8 for C. uhleri, T. pallidovirens, and N. viridula, respectively. For C. uhleri, life table calculations produced a value of 56.7 d for mean generation time ( T o ), 24.89 for net reproductive rate ( R o ) and 0.057 for the intrinsic rate of increase ( r ). Thyanta pallidovirens had a T o of 39.9 d, a R o of 81.10 and a r of 0.11. The results are discussed with respect to the improvement of IPM in California pistachios, and the information presented may contribute to the control of these pest species in other ecosystems.